(untitled) (Journal of actual problems of jurisprudence, 2020)
The current study examined the genetic and environmental architecture of early life parent-child relations and intimate partner relationship quality later in life. A series of univariate ACE and bivariate Cholesky decomposition models were fitted to a sample of monozygotic and same-sex dizygotic twins drawn from the Midlife in the United States Study (MIDUS) in order to explore the extent to which genetic factors explain individual differences in mother- and father-child relationship quality and selfreports of intimate partner relationship quality. Results revealed that genetic factors explained variation in reports of parent-child relationship quality (41% to 65%), adult intimate partner relationship quality (34%) and the covariance between the two (81% to 83%). Nonshared environmental factors accounted for the remaining covariance. Findings from the present study suggest that similar genetically influenced characteristics that account for variation in early life parent-child relations are also implicating in explaining variation in healthy intimate partner formation later in life. The implications of these findings for future research on intimate partner relationship quality and family formation are discussing. Key words: parent-child relations, intimate partner relationship quality, behavioral genetics, adult relationships.